What are the experiences of seeking, receiving and providing FGM-related healthcare?: perspectives of health professionals and women/girls who have undergone FGM: protocol for a systematic review of qualitative evidence - Evans, Catrin; Tweheyo, Ritah; McGarry, Julie; Eldridge, Jeanette; McCormick, Carol; Nkoyo, Valentine; Higginbottom, Gina M.A. (BMJ Publishing Group Ltd, 2017)
Introduction: Female Genital Mutilation (FGM) is an issue of global concern. High levels of migration mean that healthcare systems in higher-income western countries are increasingly being challenged to respond to the care needs of affected communities. Research has identified significant challenges in the provision of, and access to, FGM-related healthcare. There is a lack of confidence and competence among health professionals in providing appropriate care, suggesting an urgent need for evidence-based service development in this area. This study will involve two systematic reviews of qualitative evidence to explore the experiences, needs, barriers and facilitators to seeking and providing FGM-related healthcare in high income (OECD) countries, from the perspectives of: (1) women and girls who have undergone FGM and (2) health professionals.